DEVELOPMENT OF INTERACTIVE TEACHING MATERIALS (3D PAGE FLIP) ON SCIENCE LEARNING FOR JUNIOR HIGH SCHOOL STUDENTS IN KECAMATAN PINGGIR-MANDAU - Fidya Witria A. S; Lely Grasela M (ISER (Indonesian Science Education Research), 2020)
This study aims to: a) to find out the validity of interactive teaching materials (3D Page Flip) by experts, b) to find out the validity of interactive teaching materials (3D Page Flip) by the audience. In this study also using a limited method (RnD), namely Limited Research and Development, namely by using two media experts and 10 junior high school students in The District Edge-Mandau grade VIII. The process of media development starts from media planning, media creation according to design, experiments and also revisions of the results of the experiment, in the process of developing interactive learning media (3D Page Flip) requires an application assistance in its implementation of 3D page flip application. In this study the instrument was given to two expert lecturers with a result of 81.6% with valid validation, feasible, appropriate and without revision. Instruments were also given to an audience of 10 junior high school students in grade VIII at SMP Subdistrict Pinggir- Mandau with a validation score of 95% with very valid results, very suitable and without refisi. The conclusion of this research is interactive teaching material (3D Page Flip) in science subjects in junior high school grade VIII semester 1 can be used as teaching materials in junior high school.